Digital PCR Validation for Characterization of Quantitative Reference Material of Escherichia coli O157:H7 Genomic DNA - Claudia Patricia Tere-Peña; Martha Nancy Calderon-Ozuna; John Emerson Leguizamón Guerrero (Methods and Protocols)
Escherichia coli O157:H7, a Shiga-toxin-producing E. coli (STEC), is an important pathogen related to foodborne disease that is responsible for a growing number of outbreaks worldwide and has been detected in processed meats, dairy, and fresh vegetables. Although culturing is the gold standard method for detection of this bacterium, molecular methods based on nucleic acid amplification techniques such as PCR are becoming more common because of their rapidity, sensitivity, and specificity. However, to ensure reliable results among the several alternative PCR protocols (e.g., commercial kits and reference methods), different measurement assurance tools, including validated methods, reference materials, and proficiency tests, among others, are required. Herein, we present a digital PCR method validation for E. coli O157:H7 detection and quantification using seven specific gene sequences; this method quantified nucleic acids from different E. coli serotypes, with a detection range of 6.6 to 7900 copies/µL and a repeatability standard deviation over the concentration range of 1% to 13.6%. The relative standard uncertainty was 3.5–14.6%, and the detection limit was 0.27 copies/µL. Subsequently, two batches of a candidate reference material based on E. coli O157:H7 genomic DNA were then produced and characterized for evaluation of copy number concentration with the validated ddPCR method, with assigned values of 164,770 ± 9251 and 172 ± 9 copies/μL. Thus, this study demonstrated the development of a validated method and reference material for dPCR and qPCR detection of E. coli O157:H7, a key STEC responsible for food poisoning.